Pengetahuan Ibu Rumah Tangga tentang Kolesterol dan Penggunaan Minyak Jelantah (Waste Cooking Oil) di Desa Neglasari Kecamatan Bojong Picung Cianjur - Nadirawati; Muthmainah, Nia Naelah (Jurnal Keperawatan Soedirman, 2010)
Cholesterol has been known as a main cause of atherosclerosis disease, of which calcification and ossification process occurrence in vein wall. These processes, therefore, affect vein channel especially coronary blood vessel narrowing and cover the blood stream in it. This situation is increasing risk of coroner heart disease. Negla Sari village experiences an increase in incidence relating to high-cholesterol of Â±5.6% such as atherosclerosis, heart disease, and stroke. The increase level is higher than other village, moreover, the residents often use wasted cooking oil is doubted if their habitual of using wasted cooking oil affect the increase of high-cholesterol. Objective of this study is to find out knowledge of housewives about cholesterol and utilization of wasted cooking oil in Negla Sari of Bojong Picung district - Cianjur. The study applies descriptive research method in the course of co-relational descriptive. From 1536 of total population, there are 94 respondents of housewives in Negla Sari of Bojong Picung district â€“ Cianjur that are taken as sample through random sampling technique. Data collection is done by disseminating questionnaires and the data is then analyzed in two steps of univariate and bivariate. Base research result is known mother knowledge hits cholesterol of a large part of (52.1%) is on category less, temporary at variable the usage of waste cooking oil a large part of is on category use waste cooking oil (62.8 %). Result of relation bivariate test between knowledge and the usage of waste cooking oil is obtained p-value 0.027 that mean existed relation between mother knowledge hit cholesterol and the usage of waste cooking oil. Suggested to public health centre can improve health role at family especially housewife, and to society specially housewife more proactive to follow in activity of health construction, that given to exploit information source maybe, that have the character of direct or indirect either that that have the shape of media print or electronic to add mother knowledge specially hits cholesterol with the usage of waste cooking oil.